Enhancing Realism in Simulated Prosthetic Vision by Introducing Temporal Models - Tomás Barba, Julia; Pérez Yus, Alejandro; Bermúdez Cameo, Jesús; Guerrero, José J. (Jornada de Jóvenes Investigadores del I3A, 2024)
Recent studies have demonstrated the effectiveness of computer vision techniques in assisting patients with visual prostheses. Evaluating these techniques requires the use of Simulated Prosthetic Vision (SPV). In this work, we propose an approach that introduces biologically-inspired temporal models to enhance the realism of SPV in real-time experimental frameworks.